2019
DOI: 10.1037/rep0000281
|View full text |Cite
|
Sign up to set email alerts
|

Meaning in life and physical quality of life: Cross-lagged associations during inpatient rehabilitation.

Abstract: Objectives: This study investigated reciprocal associations between meaning in life and physical quality of life (QOL) in the rehabilitation context. It was hypothesized that a higher level of meaning in life at Time 1 (T1) would predict better physical QOL at Time 2 (T2), and that better physical QOL (T1) would predict a higher level of meaning in life (T2). Research Method: This longitudinal study enrolled 339 participants (aged 19–84 years, 57.9% women) who provided self-report data (T1) at the beginning of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Health-related quality of life research is a burgeoning area (Brazier & Tsuchiya, 2015;Cummins et al, 2004;Salvador-Carulla et al, 2014) and involves a reciprocal relationship between health status and well-being, with affect correlating with symptom checklists (Krampen, 1999), physical functioning, pain and general health (Czekierda et al, 2019;Karimi & Brazier, 2016). The relationship also appears to be bidirectional, with people that present with heart disease, arthritis, and lung disease having increased levels of depressed mood and impaired hedonic and eudemonic wellbeing (Boehm & Kubzansky, 2012;Steptoe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Health-related quality of life research is a burgeoning area (Brazier & Tsuchiya, 2015;Cummins et al, 2004;Salvador-Carulla et al, 2014) and involves a reciprocal relationship between health status and well-being, with affect correlating with symptom checklists (Krampen, 1999), physical functioning, pain and general health (Czekierda et al, 2019;Karimi & Brazier, 2016). The relationship also appears to be bidirectional, with people that present with heart disease, arthritis, and lung disease having increased levels of depressed mood and impaired hedonic and eudemonic wellbeing (Boehm & Kubzansky, 2012;Steptoe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A study of MIL and quality of life after recovery showed that MIL can promote motivation to exercise, which can lead to recovery and improve the quality of life. A rehabilitation study showed that logotherapy is the basis for many psychotherapies ( 22 ). This study’s findings may reflect the sense of MIL that can give people a positive attitude toward life, a better social network, and thus a better quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Sources of meaning can actively promote MIL and shift an individual’s life attitude from negative to positive ( 21 ). Therefore, by integrating family support into older adults’ daily life and developing initiatives that promote healthy surroundings, such as social connectedness, co-residential living, and special care for those who are physically disabled, we can protect older adults against late-life depression ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Outra questão a ser destacada é concernente a futuras ampliações da publicidade destas pesquisas por parte dos periódicos de Psicologia, pois as revistas da área de Educação prevaleceram neste levantamento. Quanto ao delineamento dos estudos, observou-se que somente um estudo foi longitudinal (E6), o que indica a demanda de mais pesquisas que avaliem como o sentido de vida impacta outras variáveis ou constructos psicológicos ao longo do tempo (Czekierda et al, 2019;Tostes et al, 2018).…”
Section: Discussionunclassified